1994
DOI: 10.21273/hortsci.29.12.1514
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Irrigation Reduces Container Leachate Nitrate-nitrogen Concentration

Abstract: Two experiments were conducted to evaluate the effects of cyclic irrigation on leachate NO3-N concentration, container leachate volume, total effluent volume, and growth of Ilex crenata Thunb. `Compacta'. In Expt. 1, container leachate volume was reduced 34% when 13 mm of water was applied in three cycles compared to continuous irrigation of 13 mm per unit time. Forty-nine percent less container leachate volume was collected from a continuous application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 4 publications
3
42
1
2
Order By: Relevance
“…'Prairifire' (Prairifire crabapple), Cercis canadensis L. (Eastern redbud), and Acer ·freemai 'Jeffersred' (Autumn Blaze Ò maple), respectively, when grown outdoors and fertilized with CRF. Reduction of LF is another approach to improve nutrient use efficiency (Fare et al, 1994;McGinnis, 2007;Owen et al, 2008;Tyler et al, 1996). Leaching fraction reduction results in decreased nutrient effluent volume and content.…”
Section: Resultsmentioning
confidence: 99%
“…'Prairifire' (Prairifire crabapple), Cercis canadensis L. (Eastern redbud), and Acer ·freemai 'Jeffersred' (Autumn Blaze Ò maple), respectively, when grown outdoors and fertilized with CRF. Reduction of LF is another approach to improve nutrient use efficiency (Fare et al, 1994;McGinnis, 2007;Owen et al, 2008;Tyler et al, 1996). Leaching fraction reduction results in decreased nutrient effluent volume and content.…”
Section: Resultsmentioning
confidence: 99%
“…In many studies only the leaching of NO 3 –N has been measured (Rathier and Frink, 1989; Fare et al, 1994; Broschat, 1995; Andersen and Hansen, 2000), obviously because the NO 3 –N levels of 10 mg L −1 (USEPA, 2001) or NO 3 levels of 50 mg L −1 (NO 3 –N 11.3 mg L −1 ) (European Community, 1998) in drinking water are considered unsafe for humans. In our study, however, the amounts of NO 3 –N in leachates covered only 25 to 54% of the total N leached.…”
Section: Discussionmentioning
confidence: 99%
“…During production of container seedlings, a potential risk for nutrient leaching exists, as large volumes of irrigation water are used, and in many countries nearly all fertilizers are applied in liquid form through irrigation systems (fertigated) (Landis et al, 1989; Dumroese et al, 1995). Among other things, the influence of irrigation volume, application method, and fertilizer type on leaching of water and nutrients has been studied with different horticultural crops (Hershey and Paul, 1982; Rathier and Frink, 1989; McAvoy et al, 1992; Fare et al, 1994; Broschat, 1995; Andersen and Hansen, 2000). However, most of the crops studied have been grown in large, individual pots, one to five liters in volume, while forest seedlings are grown in small pots, 40 to 300 mL in volume.…”
mentioning
confidence: 99%
“…In a container production of Ilex crenata Thunb. 'Compacta', Fare et al [19] reported that the percentage of applied N leached as NO 3 ─N ranged from 46% when 13-mm irrigation was applied in 3 cycles to 63% when 13-mm irrigation was applied in a single cycle. Broschat [20] investigated N leaching from a container substrate comprised of 50% pine bark, 40% sedge peat and 10% sand and reported 3710 mg of NO 3 ─N could be leached per container during a 6-month production of Spathiphyllum Schott.…”
Section: Nitrogen Loss During Container Plant Productionmentioning
confidence: 99%